2013
DOI: 10.1111/pin.12041
|View full text |Cite
|
Sign up to set email alerts
|

Complement split product C4d deposition in placenta in systemic lupus erythematosus and pregnancy‐induced hypertension

Abstract: Systemic lupus erythematosus (SLE) and pregnancy-induced hypertension (PIH) are related to premature delivery and intrauterine growth restriction (IUGR), and share histological findings of the placenta. Association with complement dysregulation has been reported in pregnancy for both disorders. The purpose of this study was to investigate the utility of C4d immunohistochemistry for placentas with SLE- and PIH-associated pregnancy. C4d staining was performed on paraffin-embedded tissue of placentas from 26 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…A study conducted by Minamiguchi et al [21] indicated that the degree of C4d immunoreactivity was associated with low placental weight and histological placental abnormalities among individuals with PIH, as well as among those with SLE. Activation of the complement cascade may result in placental dysfunction in cases of PIH and in cases of SLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Minamiguchi et al [21] indicated that the degree of C4d immunoreactivity was associated with low placental weight and histological placental abnormalities among individuals with PIH, as well as among those with SLE. Activation of the complement cascade may result in placental dysfunction in cases of PIH and in cases of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that alterations in the immune system that are associated with preterm delivery may be implicated in an increased risk for developing autoimmune diseases. For example, C4d immunoreactivity is related to low placental weight and preterm birth [21,22] and is also involved in the pathogenesis of SLE. [21] Interestingly, a population-based cohort study indicated that nulliparous women and 1-child mothers display a markedly increased risk for developing SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse C4d staining at the feto-maternal interface was present almost exclusively in patients with SLE and/or APS and was related to intrauterine fetal death [37]. Dramatically increased immunohistochemistry staining of C-4d was statistically associated with low-placental weights and low birth weight in SLE patients [38].…”
Section: C4d Deposition In Tissues In Sle Patientsmentioning
confidence: 94%
“…Adverse events during pregnancy [35][36][37] Renal tissue Related to the presence of microthrombosis and histopathological classification of lupus nephritis [38,42] No relationship with disease activity, histological activity and chronicity of lupus nephritis [41,43,44] …”
Section: Placentasmentioning
confidence: 99%